Effects of drought stress on antioxidant enzymes in common bean (Phaseolus vulgaris L.) seedlings (Bangladesh Journal of Botany, 2021)
Drought is one of the most severe environmental constraints which reduces common bean production worldwide. Exploration of the physiological mechanism of common bean under drought stress is important for the efficient production and variety selection of common beans. In the present study, non-droughtresistant variety (Longyundou10) and drought-resistant variety (Longyundou17) were identified to elucidate the effects of drought stress on antioxidant system of common beans at seedling stage. Under drought stress, APX and SOD activities showed a single peak curve that first increased and then decreased, and the dynamic changes of CAT and POD activities were more complicated. Under different levels of drought treatment, the average values of APX, SOD, CAT and POD activities of common bean were found to be higher than those of normal water conditions, and the average values were the highest under severe drought stress, indicating that these antioxidant enzymes were stimulated under drought stress.Bangladesh J. Bot. 50(3): 873-878, 2021 (September) Special